Body Mass Index and Decline of Cognitive Function - Kim, Sujin (PLoS One, 2016)
BACKGROUND: The association between body mass index (BMI) and cognitive function is a public health issue. This study investigated the relationship between obesity and cognitive impairment which was assessed by the Korean version of the Mini-mental state examination (K-MMSE) among mid- and old-aged people in South Korea. METHODS: A cohort of 5,125 adults, age 45 or older with normal cognitive function (K-MMSE≥24) at baseline (2006), was derived from the Korean Longitudinal Study of Aging (KLoSA) 2006~2012. The association between baseline BMI and risk of cognitive impairment was assessed using multiple logistic regression models. We also assessed baseline BMI and change of cognitive function over the 6-year follow-up using multiple linear regressions. RESULTS: During the follow-up, 358 cases of severe cognitive impairment were identified. Those with baseline BMI≥25 kg/m(2) than normal-weight (18.5≤BMI<23 kg/m(2)) were marginally less likely to experience the development of severe cognitive impairment (adjusted odds ratio [aOR] = 0.73, 95% CI = 0.52 to 1.03; P(trend) = 0.03). This relationship was stronger among female (aOR = 0.63, 95% CI = 0.40 to 1.00; P(trend) = 0.01) and participants with low-normal K-MMSE score (MMSE: 24–26) at baseline (aOR = 0.59, 95% CI = 0.35 to 0.98; P(trend)<0.01). In addition, a slower decline of cognitive function was observed in obese individuals than those with normal weight, especially among women and those with low-normal K-MMSE score at baseline. CONCLUSION: In this nationally representative study, we found that obesity was associated with lower risk of cognitive decline among mid- and old-age population.